Wielkie imprezy sportowe w służbie budowania wizerunku państw. Przykład grupy BRIC - Jakubowski, Jakub (My University, 2012)
the article shows a role of Big sporting events as a tool of advancement and development of a state, taking Brasil, Russia, India and China into account. The mechanisms of creating the state image are discussed. Moreover, some examples of using sport by BRIC group countries are underlined. Finally, the process of commercialisation and its influence on Olympic Games values are depicted.
Keywords: sport; polityka; BRIC